THE RESTITUTION TRIANGLE STRATEGY IN ESTABLISHING A SELF-DIRECTED LEARNING PARADIGM BASED ON ACTIVE AWARENESS - Akhmad Ghasi Pathollah; Asia Anis Sulalah; Desi Susanti; Hasan Jali (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aimed to explore a Restitution Triangle Strategy as an innovative approach in building a Self-Directed Learning (SDL) paradigm with a focus on increasing students' active awareness. The research method used is a qualitative study with a model development approach through observation, interviews, and literature study. The results of the study show that the restitution triangle strategy is able to construct students' active awareness, which contributes to the achievement of a more sustainable SDL paradigm. The application of this strategy harmoniously integrate psychological and pedagogical aspects in learning, which supports student learning independence. In addition, this study also found that educators need training to apply this strategy effectively. The implementation of this strategy also shows an increase in student participation and emotional involvement in learning. The use of this approach demonstrates the importance of learning management that prioritizes acknowledgement, reflection, and compensation. The implication of this study is the importance of applying the Restitution Triangle strategy in developing an active awareness-based Self-Directed Learning paradigm, which can increase student engagement in the learning process and encourage the development of independent skills in facing educational challenges.